(untitled) (Fiep Bulletin - online, 2014)
Futsal is a sport where the time to analyze, evaluate, elaborate and execute is limited when compared to other team sports (Schmidt et al., 2000). Futsal is particularly suitable for children in the period 9-10 years who are learning the specific techniques of play. In futsal, one of the most important variables to execute an effective action, it is the time needed by the athlete to complete his movement (Nicoletti and Borghi, 1992). In addition, motor imagery (Sanders et al., 2004 and Bandura, 1997) may be learned quality motor skills if they are included in the weekly instructional program. The purpose of the research is to verify if in a sample group, to which is subjected the vision of its movies and models executive engines, there are better learning of specific techniques as compared to a control group to which, however, is not subject to any view movies. The pilot study is carried out on 20 players (9-10 years old) of a team that is training two times a week for a year. Only 10 on 20 players, before a workout, is subjected watching video-analyzed movies, depicting a correct model of execution carried out by a high-level futsal player. Players are divided into 2 groups with similar technical characteristics; they are tested in the beginning, during and at the end of the study on three typical technical gestures chosen from the basic game (controlling the ballstopping the ball with the sole of the foot; guiding the ball-movement of the ball; shot-kicking the ball with the toe). Significant increases in the execution of the technical gestures should be found in sample group. In case of a positive data we will assume the use of video analysis as well as teaching methodology as a valid instrument for the evaluation of motor skills.